2002
DOI: 10.1055/s-2002-19275
|View full text |Cite
|
Sign up to set email alerts
|

The Ratio HLa : RPE as a Tool to Appreciate Overreaching in Young High-Level Middle-Distance Runners

Abstract: The purpose of the present investigation was to study the effects of eight weeks of intensive training at the beginning of the athletic season on perceived exertion and on the ratio of blood lactate concentration to ratings of perceived exertion (HLa : RPE) in young runners. Eight high-level middle-distance runners performed two exhausting exercises on an indoor track before and after eight weeks of training. The first test was an incremental exercise to determine their maximal oxygen uptake (VO(2) max), the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 27 publications
1
30
0
1
Order By: Relevance
“…It implies that there was a close relationship between hardness and exhaustion time during exercises to exhaustion, whatever the sex. Such a result has been already mentioned in previous research during incremental exercise after training [15]. This means that although RPE and ETL do not give the same information, they are probably mediated by the same factors.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It implies that there was a close relationship between hardness and exhaustion time during exercises to exhaustion, whatever the sex. Such a result has been already mentioned in previous research during incremental exercise after training [15]. This means that although RPE and ETL do not give the same information, they are probably mediated by the same factors.…”
Section: Discussionsupporting
confidence: 62%
“…According to the performances of these athletes, the initial velocity was set at 14 km · h -1 and was increased by one km · h -1 every three minutes until 17 km · h -1 was attained [15]. Each stage was separated by a 30-s rest period.…”
Section: Experimental Designmentioning
confidence: 99%
“…This decline in the [La - ]/RPE ratio was explained by a reduction in [La - ], whereas RPE remained stable. More recently, Garcin et al [14] confirmed this result in high-level middle-distance runners. It may therefore be interesting to use the [La - ]/RPE ratio to help detect overreaching or overtraining in modern karate, but further studies must first be conducted.…”
Section: Discussionmentioning
confidence: 73%
“…Perception of effort, mood states and several behavioral indicators have been proven to be affected by overtraining and hence are the psychological constructs that have most often been taken into account in the evaluation of overtraining. Garcin, Fleury, and Billat (2002), using the Perceived Exertion Scale (RPE; Borg, 1970), found that overtrained subjects had a perception of greater effort than individuals who were not overtrained. However, the effectiveness of using scales that measure effort in isolation for the diagnosis of overtraining has been questioned (Urhausen & Kindermann, 2002).…”
mentioning
confidence: 99%